Correction: Ultrathin porous NiO nanoflake arrays on nickel foam as an advanced electrode for high performance asymmetric supercapacitors. Issue 24 (2nd June 2016) - Wu, Shuxing; Hui, K. S.; Hui, K. N.; Kim, Kwang Ho
Abstract : Correction for 'Ultrathin porous NiO nanoflake arrays on nickel foam as an advanced electrode for high performance asymmetric supercapacitors' by Shuxing Wu et al., J. Mater. Chem. A, 2016, DOI: ; Web:10.1039/c6ta02005d .